2021
DOI: 10.1093/jac/dkab385
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of HIV-1 reveals extensive subtype variation and drug resistance after failure of first-line antiretroviral regimens in Nigeria

Abstract: Background Deep sequencing could improve understanding of HIV treatment failure and viral population dynamics. However, this tool is often inaccessible in low- and middle-income countries. Objectives To determine the genetic patterns of resistance emerging in West African HIV-1 subtypes during first-line virological failure, and the implications for future antiretroviral options. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
12
2
Order By: Relevance
“…27 Other treatment regimens that are being evaluated for low-income countries to improve adherence and tolerability, and limit pill burden include long-acting injectable cabotegravir-rilpivirine which has shown on modeling studies to be cost-effective in PWH with an HIV VL of more than 1000 copies/mL but there is concern for potentially inducing integrase inhibitor resistance. 24,28 This paper complements the literature to help characterize common barriers to HIV care among people living with HIV in the DR and the greater Caribbean region. Risk factors for non-adherence to ART found in other urban regions of the DR (Santo Domingo and Puerto Plata) included heavy alcohol use, having children and perceptions of less social support.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…27 Other treatment regimens that are being evaluated for low-income countries to improve adherence and tolerability, and limit pill burden include long-acting injectable cabotegravir-rilpivirine which has shown on modeling studies to be cost-effective in PWH with an HIV VL of more than 1000 copies/mL but there is concern for potentially inducing integrase inhibitor resistance. 24,28 This paper complements the literature to help characterize common barriers to HIV care among people living with HIV in the DR and the greater Caribbean region. Risk factors for non-adherence to ART found in other urban regions of the DR (Santo Domingo and Puerto Plata) included heavy alcohol use, having children and perceptions of less social support.…”
Section: Discussionmentioning
confidence: 94%
“…Patients who are on second-line regimens are more likely to be at risk for virologic failure due to existing difficulties with ART adherence and possibly undiagnosed drug resistance. 22 24 Other contributing factors include the greater pill burden, more complicated dosing schedules, and higher rates of adverse effects known to be associated with PI-based regimens. 25 , 26 Access to genotype testing is limited for PWH in the DR, and ART regimens are frequently changed based on HIV disease progression, lack of viral suppression and the availability of medications in the hospital pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited available sequencing data, and the available sequences are mostly partial sequences derived from molecular epidemiology studies focusing on drug resistance analyses. Previous studies showed that subtype G and CRF02_AG were the predominant HIV-1 strains in Nigeria, although the transmission of CRF06_cpx was also observed [ 30 , 31 , 32 , 33 , 34 , 35 ]. The co-circulation of these strains could have potentially resulted in the generation of the CRF91_cpx strain.…”
Section: Discussionmentioning
confidence: 99%